STATE AUTHORITY IN LAND CONTROL: CONSTITUTIONAL ANALYSIS OF THE IMPLEMENTATION OF ARTICLE 33 PARAGRAPH 3 OF THE 1945 CONSTITUTION - Rizky, Ahmad Valdo; Isnawati; Putri, Dina Paramitha Hefni; Ismail, Rezky Robiatul Aisyiah (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This study seeks to explore comprehensively the application of Article 33 paragraph (3) of the 1945 Constitution, which governs the state’s authority over land ownership, through philosophical, historical, and sociological lenses. Philosophically, the notion of state control over the earth, air, and natural resources underscores the role of the state as the supreme steward entrusted with managing these assets for the collective welfare of its citizens, rather than as a private proprietor. This principle reflects the ideals of social justice that were abolished in the values of Pancasila. Historically, the transformation from the colonial concept of domein verklaring to the UUPA system illustrates a shift in the paradigm of land management in order to affirm the nation's rights to natural resources. Sociologically, the state is present as a regulator to guarantee fair land distribution and the protection of community rights, including customary rights, amidst the dynamics of economic growth and urbanization. The constitutional mandate contained in Article 33 paragraph (3) of the 1945 Constitution affirms that every land governance policy should prioritize the prosperity of the people by ensuring harmony between private rights and collective interests, while simultaneously preventing the concentration of ownership and potential land-related disputes.